PENERAPAN MEDIA REALIA DALAM PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Manai, Ramdani; Muda, Lisdawati; Iskandar, Karmila (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
AbstractThis research aims to find out the results of applying realia media in thematic learning to improve the learning outcomes of grade 3 students at SDN 9 Limboto. This research method is Classroom Action Research (PTK) which was carried out in class 3 of SDN 9 Limboto. The subjects in the research were 15 grade 3 students at SDN 9 Limboto, consisting of 8 boys and 7 girls. Data collection was carried out using observation, tests and documentation. The results of this research show that using realia media in thematic learning can improve student learning outcomes, observation results of student activities, and observation results of teacher activities. In the first cycle, only 5 students (33.3%) achieved the KKM score (70), while 15 students (66.6%) were below the KKM score. Cycle II showed that 9 students (60%) achieved the KKM score, the other 6 students (40%) had not yet achieved the KKM. and in cycle III, only 3 students (20%) did not reach the KKM, while the other 12 students (80%) whose scores reached the KKM. Meanwhile, for the results of the student activity observation sheet in cycle I, the results were 43.3 which was categorized as less active, then increased in cycle II was 56.6 which was quite active and in cycle III it increased with a result of 68.3 which was categorized as active. Furthermore, the results of the teacher activity observation sheet in cycle I obtained a result of 53.3 (sufficient) then it increased in cycle II with a result of 58.3 (sufficient) and in cycle III it increased with a result of 78.3 (active). Thus it can be concluded from the research results that there is an increase in results student learning. This proves that applying realia media can improve student learning outcomes and has been going well and can support increased learning outcomes.Keywords: Realia media, learning outcomes, thematic learning.Abstrak Penelitian ini bertujuan untuk mengetahui hasil penerapan media realia dalam pembelajaran tematik dapat meningkatkan hasil belajar siswa kelas 3 SDN 9 Limboto. Metode penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang dilakukan dikelas 3 SDN 9 Limboto. Subjek pada penelitian adalah siswa kelas 3 SDN 9 Limboto yang berjumlah 15 siswa, terdiri dari 8 orang laki-laki dan perempuan berjumlah 7 orang. Pengumpulan data dilakukan dengan menggunakan observasi, tes, dan dokumentasi. Hasil dari penelitian ini menunjukkan bahwa dengan menggunakan media realia dalam pembelajaran tematik dapat meningkatkan hasil belajar siswa, hasil observasi kegiatan siswa, dan hasil observasi kegiatan guru. pada siklus I hanya 5 siswa (33,3%) yang mencapai nilai KKM (70), sedangkan 15 siswa (66.6%) dibawah nilai KKM. Siklus II menunjukan bahwa 9 siswa (60%) mencapai nilai KKM, 6 siswa (40%) lainnya belum mencapai KKM. dan siklus III hanya 3 siswa (20%) yang tidak mencapai KKM, sementara 12 siswa (80%) lainya yang nilainya mencapai KKM.Sedangkan untuk hasil lembar observasi kegiatan siswa pada siklus I memperoleh hasil 43.3 yang di kategorikan kurang aktif, kemudian meningkat pada siklus II menjadi 56.6 menjadi cukup aktif dan pada siklus III meningkat dengan hasil 68.3 yang di kategorikan aktif. Selanjutnya untuk hasil lembar observasi kegiatan guru pada siklus I memperoleh hasil 53.3 (cukup) kemudian meningkat padas siklus II dengan hasil 58.3(cukup) dan pada siklus III meningkat dengan hasil 78.3(aktif) .Dengan demikian dapat disimpulkan Dari hasil penelitian menunjukkan adanya peningkatan hasil belajar siswa. Hal ini membuktikan bahwa menerapkan media realia dapat meningkatkan hasil belajar siswa telah berlangsung dengan baik dan dapat menunjang peningkatan hasil belajar.Kata Kunci: Media realia, Hasil Belajar,Pembelajaran tematik.